Cytoplasm-Translocated Ku70/80 Complex Sensing of HBV DNA Induces Hepatitis-Associated Chemokine Secretion - Li, Young; Wu, Yang; Zheng, Xiaohu; Cong, Jingjing; Liu, Yanyan; Li, Jiabin; Sun, Rui; Tian, Zhigang G.; Wei, Haiming M. (Frontiers in Immunology, 2016)
Chronic hepatitis B virus (HBV) infection remains a serious disease, mainly due to its severe pathological consequences, which are difficult to cure using current therapies. When the immune system responds to hepatocytes experiencing rapid HBV replication, effector cells (such as HBV-specific CD8+ T cells, NK cells, NKT cells, and other subtypes of immune cells) infiltrate the liver and cause hepatitis. However, the precise recruitment of these cells remains unclear. In the present study, we found that the cytoplasm-translocated Ku70/80 complex in liver-derived cells sensed cytosolic HBV DNA and promoted hepatitis-associated chemokine secretion. Upon sensing HBV DNA, DNA-dependent protein kinase catalytic subunit and PARP1 were assembled. Then, IRF1 was activated and translocated into the nucleus, which upregulated CCL3 and CCL5 expression. Because CCR5, a major chemokine receptor for CCL3 and CCL5, is known to be critical in hepatitis B, Ku70/80 sensing of HBV DNA likely plays a critical role in immune cell recruitment in response to HBV infection.